(untitled) (Research, Society and Development, 2021)
Exfoliative cytology screening for genotoxicity is an important strategy for mitigating tobacco-induced carcinogenesis. The aim of this study was to determine the frequency of micronuclei in oral epithelial cells of smoking and non-smoking patients. Sixteen volunteers, of both sexes, 40-60 years old, with healthy oral mucosa were divided into smoking or non-smoking group. Cytological smears of buccal mucosa, lateral border of the tongue and floor of the mouth stained by Pap stain allowed evaluation of 4800 microscopic images. Frequencies of micronucleated cells (MNC) and micronuclei/cell (MN/C) were compared by group, anatomical region, sex and age range, using the two-way ANOVA test followed by Tukey (p<0.05). There was a greater presence of MNC in the smoker than in the non-smoker group, with significant differences for floor of mouth, female gender and age range of 50-60 years. The amount of 1 or 2 MN/C was greater than 3 or ≥4 MN/C, especially in the smoking group. There were differences in the frequency of MN/C between smokers and non-smokers, for the three oral regions, for both sexes although more accentuated in women, and for the age range of 50-60 years beyond the age range of 40-50 years for the non-smoking group. Differences in MNC and MN/C according to oral regions, sex and age between smokers and non-smokers contribute to understand the genotoxicity mediated by tobacco.